Radiative cooling with thermoelectric for power generation - Tang, Nicholas Kah Fai (2022)
Electricity is one of the many energies that are needed by human beings in this 21st century. Thermoelectric generators (TEG) are solid-state semiconductor devices that utilize the Seebeck effect which is able to produce electricity by harvesting energy from the heat flux. Temperature difference across the semiconductors lead to the production of power. Radiative cooling can be implemented together with thermoelectric generators for power generation as it is a passive cooling method that requires no external energy source. This project aims to develop a simple prototype model of radiative cooling-thermoelectric generator. This project can contribute to the studies of methods to generate power without harming the environment radiative cooling with thermoelectric for power generation can be used for all day application and radiative cooling requires no external energy source. Furthermore, to understand different materials used for radiative cooling and their performance. Silicon dioxide (SiO2) and titanium dioxide (TiO2) was chosen as the materials for the radiative cooling coating. Both SiO2 and TiO2 were characterized using scanning electron microscope with energy dispersive X-ray (SEM) and X-ray diffraction (XRD). Three prototypes of the different radiative coating were developed in this project. Prototype A which had single-layer SiO2 coating, Prototype B which had singlelayer TiO2 coating and Prototype C which had double-layer radiative coating with SiO2 coating as the bottom layer and TiO2 coating as the top layer. A few parameters were studied throughout this project, and they are the temperature of the hot and cold sides of the TEG modules, the voltage generated by the prototypes and power generated. Data was captured for 24 hours for each prototype. From the experimental results, prototype C which is the prototype with a double-layer radiative cooling coating showed to have performed better than the other two prototypes. Prototype C managed to generate a peak voltage of 96.5 mV and the average voltage generated was 29.2 mV. Furthermore, the average temperature difference for prototype C was 1.4 °C and the average power generated was 0.655 mW. Prototype C had a 267.98% increase in terms of performance for average power generation and a 93.74% increase in terms of performance for average voltage generated as compared to prototype A.